LoRa Communication Quality Optimization on Agriculture Based on the PHY Anti-Frame Loss Mechanism - Qiufang Dai; Ziwei Chen; Guanfa Wu; Zhen Li; Shilei Lv; Weicheng Huang (Agriculture, 2024)
Agricultural environments are usually characterized by height differences and tree shading, which pose challenges for communication in smart agriculture. This study focuses on optimizing the packet loss rate and power consumption of LoRa’s practical communication quality. The research includes the investigation of the PHY anti-frame loss mechanism, encompassing PHY frame loss detection and the response mechanism between gateways and nodes. By implementing a closed loop for transmission and reception, the study enhances the communication network’s resistance to interference and security. Theoretical performance calculations for the SX1278 radio frequency chip were conducted under different parameters to determine the optimal energy efficiency, reducing unnecessary energy waste. An experimental assessment of the packet loss rate was conducted to validate the practical efficacy of the research findings. The results show that the LoRa communication with the anti-frame loss mechanism and the optimal energy ratio parameter exhibits an adequate performance. In the presence of strong and weak interferences, the reception rates are maximally improved by 37.8% and 53.4%, with effective distances of 250 m and 600 m, corresponding to enhancements of 100 m and 400 m, respectively. This research effectively reduces LoRa energy consumption, mitigates packet loss, and extends communication distances, providing insights for wireless transmission in agricultural contexts.